The effect of mutation and promotion on work spirit with job satisfaction as a mediation variable at perum bulog regional office of west sumatra - RIYAN ANERI PRATAMA; Fitria, Yuki (Human Resource Management Studies, 2023)
The purpose of this study was to determine the effects of job mutations and promotions on working psyche, with job satisfaction as a mediating variable. This research was conducted at the Perum BULOG Regional Office of West Sumatra The population of this study was staff of the Perum BULOG Regional Office of West Sumatra. While the sample used was 52 employees. Data collection was carried out by distributing online questionnaires and data processing was carried out through Smart PLS4. The results showed that job mutations and promotions had a significant positive effect on work spirit at Perum BULOG Regional Office of West Sumatra. Job satisfaction can mediate the effect of job mutations and promotion on work spirit at Perum BULOG Regional Office of West Sumatra.